Layout essentials : 100 design principles for using grids - Tondreau, Beth (Rockport Publishers, 2009)
Adhering to certain layout and grids standards and principles is important for any job from brochures, to annual reports, to posters, to websites, to publications.However, knowing how to bend the rules and make certain grids work for the job at hand takes skill.